ASSOCIATION OF HEART RATE AT HOSPITAL DISCHARGE AND REHOSPITALIZATION OF PATIENTS WITH HEART FAILURE AND REDUCED EJECTION FRACTION - Kaleem Ullah Sheikh,; Abeer Sarfaraz,; Amna Janjua,; Sana Sarfaraz,; Sana Shoaib,; Sanjna Devi, (Journal of Ayub Medical College Abbottabad, 2023)
Background: One of the major causes of cardiovascular morbidity and mortality is heart failure. The study aims to assess the effect of heart rate on the incidence of rehospitalization in patients with heart failure and reduced ejection fraction. Methods: It is a cross-sectional, analytical research conducted over six months, from June to December 2022, at the cardiology department of a tertiary care hospital. Patients who satisfied the modified Framingham heart failure criteria at admission and were discharged with an initial diagnosis of heart failure and those readmitted within 6 months or less of their discharge were included in the study. Pregnant women, patients diagnosed with cognitive impairment, and patients who had contraindications for taking any of the beta-blockers, angiotensin-converting enzyme inhibitor/angiotensin receptor blocker /angiotensin receptor -neprilysin inhibitor, Sodium-Glucose co-transport inhibitor, and mineralocorticoid inhibitors were excluded from the study. Result: A total of 77 patients were included in the study. At discharge, approximately 71 patients had a heart rate of less than 70 beats/min and had no readmissions whereas, 6 patients had a heart rate of greater than 70 beats/min with 5 patients requiring readmission in the following 6 months. This relationship was statistically significant with a p-value of 0.000. Conclusion: According to the study, heart rate is a significant factor in the rehospitalization of individuals with heart failure and a low ejection fraction. At discharge, if the heart rate is not optimized then the rate of readmissions is increased.